Pathogenesis‐directed therapy of 2019 novel coronavirus disease - Stratton, Charles W.; Tang, Yi‐Wei; Lu, Hongzhou (Journal of medical virology, 2021)
The 2019 novel coronavirus disease (COVID‐19) now is considered a global public health emergency. One of the unprecedented challenges is defining the optimal therapy for those patients with severe pneumonia and systemic manifestations of COVID‐19. The optimal therapy should be largely based on the pathogenesis of infections caused by this novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Since the onset of COVID‐19, there have been many prepublications and publications reviewing the therapy of COVID‐19 as well as many prepublications and publications reviewing the pathogenesis of SARS‐CoV‐2. However, there have been no comprehensive reviews that link COVID‐19 therapies to the pathogenic mechanisms of SARS‐CoV‐2. To link COVID‐19 therapies to pathogenic mechanisms of SARS‐CoV‐2, we performed a comprehensive search through MEDLINE, PubMed, medRxiv, EMBASE, Scopus, Google Scholar, and Web of Science using the following keywords: COVID‐19, SARS‐CoV‐2, novel 2019 coronavirus, pathology, pathologic, pathogenesis, pathophysiology, coronavirus pneumonia, coronavirus infection, coronavirus pulmonary infection, coronavirus cardiovascular infection, coronavirus gastroenteritis, coronavirus autopsy findings, viral sepsis, endotheliitis, thrombosis, coagulation abnormalities, immunology, humeral immunity, cellular immunity, inflammation, cytokine storm, superantigen, therapy, treatment, therapeutics, immune‐based therapeutics, antiviral agents, respiratory therapy, oxygen therapy, anticoagulation therapy, adjuvant therapy, and preventative therapy. Opinions expressed in this review also are based on personal experience as clinicians, authors, peer reviewers, and editors. This narrative review linking COVID‐19 therapies with pathogenic mechanisms of SARS‐CoV‐2 has resulted in six major therapeutic goals for COVID‐19 therapy based on the pathogenic mechanisms of SARS‐CoV‐2. These goals are listed below: 1. The first goal is identifying COVID‐19 patients that require both testing and therapy. This is best accomplished with a COVID‐19 molecular test from symptomatic patients as well as determining the oxygen saturation in such patients with a pulse oximeter. Whether a symptomatic respiratory illness is COVID‐19, influenza, or another respiratory pathogen, an oxygen saturation less than 90% means that the patient requires medical assistance. 2. The second goal is to correct the hypoxia. This goal generally requires hospitalization for oxygen therapy; other respiratory‐directed therapies such as prone positioning or mechanical ventilation are often used in the attempt to correct hypoxemia due to COVID‐19. 3. The third goal is to reduce the viral load of SARS‐CoV‐2. Ideally, there would be an oral antiviral agent available such as seen with the use of oseltamivir phosphate for influenza. This oral antiviral agent should be taken early in the course of SARS‐CoV‐2 infection. Such an oral agent is not available yet. Currently, two options are available for reducing the viral load of SARS‐CoV‐2. These are post‐Covid‐19 plasma with a high neutralizing antibody titer against SARS‐CoV‐2 or intravenous remdesivir; both options require hospitalization. 4. The fourth goal is to identify and address the hyperinflammation phase often seen in hospitalized COVID‐19 patients. Currently, fever with an elevated C‐reactive protein is useful for diagnosing this hyperinflammation syndrome. Low‐dose dexamethasone therapy currently is the best therapeutic approach. 5. The fifth goal is to identify and address the hypercoagulability phase seen in many hospitalized COVID‐19 patients. Patients who would benefit from anticoagulation therapy can be identified by a marked increase in d‐dimer and prothrombin time with a decrease in fibrinogen. To correct this disseminated intravascular coagulation‐like phase, anticoagulation therapy with low molecular weight heparin is preferred. Anticoagulation therapy with unfractionated heparin is preferred in COVID‐19 patients with acute kidney injuries. 6. The last goal is prophylaxis for persons who are not yet infected. Potential supplements include vitamin D and zinc. Although the data for such supplements is not extremely strong, it can be argued that almost 50% of the population worldwide has a vitamin D deficiency. Correcting this deficiency would be beneficial regardless of any impact of COVID‐19. Similarly, zinc is an important supplement that is important in one's diet regardless of any effect on SARS‐CoV‐2. As emerging therapies are found to be more effective against the SARS‐CoV‐2 pathogenic mechanisms identified, they can be substituted for those therapies presented in this review.